What kansans are learning - Creager, Phil Sheridan (My University, 1891)
Introduction: The recent political upheaval in this state has done more to set the mind of the Kansan at worst considering his condition and surroundings than anything else save the danger of imminent destruction could possibly have done. He has begun to study for himself the circumstances which have conduced to his present condition. And it is well that it is so; for while as yet we have no positive assurance that all of the provoking evils have been or will be found, yet it is morally certain that the Kansan in his search will unearth facts, the disarray and of which has done much to retard the development of the state and the prosperity of her people.
Citation: Creager, Phil Sheridan. What kansans are learning. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Politics; Upheaval; Kansas; Destruction; Theses; Manuscripts (documents)